Efficacy and Safety of Aspirin Plus Intermittent Pneumatic Compression Device vs. Low Molecular Weight Heparin as Thromboprophylaxis after Total Hip Arthroplasty: A Prospective Randomized Control Trial - Paudel, Sushil (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Total hip arthroplasty has notable risk of morbidity and mortality from venous thromboembolic events. The purpose of this study was to find out the incidences of deep vein thrombosis and pulmonary embolism in patients undergoing total hip joint arthroplasty and compare effectiveness and safety ofthromboprophylaxis with aspirin plus intermittent pneumatic compression device with that of low molecular weight heparin.METHODS: Patients who had total hip arthroplasty (unilateral/bilateral) were randomized to receive prophylaxis with aspirin plus intermittent pneumatic compression device or low molecular weight heparin. Routine screening for deep vein thrombosis with color Doppler was performed.RESULTS: 180 patients (224) joints) were randomized into 2 groups. The rates of deep venous thrombosis were 2.22% in the aspirin plus compression group compared to 0% in the low molecular weight heparin group. The rates of pulmonary embolism were 1.11 % in the Aspirin plus compression group and 0% in the heparin group, and there were no fatal pulmonary emboli. Within the six weeks and three months follow-up, no thromboembolic events occurred. The rate of major bleeding events was 1.11 % in the aspirin and compression group and 10% in the low-molecular-weight heparin group.CONCLUSIONS: An inexpensive multimodal protocol, consisting of aspirin, exercises, and the use of intermittent compression devices, was associated with low thromboembolic complications.